Türkiye’de kadına yönelik aile içi şiddet ve bireylerin kadına yönelik aile içi şiddetle ilgili görüşleri - Korkmaz, Murat; Yücel, Ali Serdar; Karta, Nurullah; Şahbudak, Ercan; Germir, Hatice Nur; Şen, Erdal; Gürkan, Ayça; Sevil, Ümran (My University, 2015)
Recently, violence against women has become at the top of the agenda and it has turned into an important problem of the society. Violence against women can be seen in different forms within the society. The purpose of this study is to determine opinions about different violence dimensions against women (physical violence, sexual violence, psychological-emotional violence, economic violence and gender mainstreaming and violence in general). Sample of the study was composed of 663 participants. A 57-item scale was used in acquiring data. Data acquired from the study was analyzed with SPSS 18 statistical program and reliability and validity were ensured. The value of 0.934 was acquired as Cronbach’s Alpha coefficient. The acquired data was subjected to Kruskal Wallis, ANOVA, Jonckheere-Terpstra Test techniques. At the end of the study, it was found that violence types showed difference by age, gender, educational status, income status and place of residence variables of the participants.

Son yıllarda sıkça gündeme gelen ve toplumun önemli bir sorunu haline dönüşen konulardan biride kadına yönelik şiddet konusudur. Kadına yönelik şiddet toplumda farklı şekillerde görülebilmektedir. Bu çalışmanın amacı kadına yönelik farklı şiddet boyutları (fiziksel şiddet, cinsel şiddet, psikolojik-duygusal şiddet, ekonomik şiddet ve toplumsal cinsiyet ve genel olarak şiddet) ile ilgili görüşlerinin belirlenmesidir. Çalışmanın örneklemini 663 katılımcı oluşturmuştur. Araştırmada verilerin elde edilmesinde 57 maddelik bir ölçek kullanılmıştır. Araştırmadan elde edilen veriler SPSS 18 istatistik programı ile analiz edilmiş, güvenirlilik geçerlilik sağlanmıştır. Cronbach’s Alpha kat sayısı olarak 0.934 değeri elde edilmiştir. Elde edilen veriler Kruskal Wallis, ANOVA, Jonckheere-Terpstra Test tekniklerine tabii tutulmuştur. Araş- tırma sonunda katılımcıların yaş, cinsiyet, eğitim durumu, gelir durumu ve yaşadıkları yer değişkenlerine göre şiddet türlerinin farklılık oluşturduğu bulunmuştur.
Domestic violence against women and opinions of individuals about domestic violence against women in Turkey
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Woman; Violence; Family; Individual; Opinion; Kadın; Şiddet; Aile